2016
DOI: 10.1088/1367-2630/18/10/103054
|View full text |Cite
|
Sign up to set email alerts
|

Epitaxial growth of thermally stable cobalt films on Au(111)

Abstract: Ferromagnetic thin films play a fundamental role in spintronic applications as a source for spin polarized carriers and in fundamental studies as ferromagnetic substrates. However, it is challenging to produce such metallic films with high structural quality and chemical purity on single crystalline substrates since the diffusion barrier across the metal-metal interface is usually smaller than the thermal activation energy necessary for smooth surface morphologies. Here, we introduce epitaxial thin Co films gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 56 publications
1
4
0
Order By: Relevance
“…Figure 1c,d shows representative STM topographic images of Co films on Au(111) surface before (1c) and after (1d) annealing. The morphology is similar to previous results [ 40,43 ] and shows that the Co film is dominated by random islands without thermal annealing but forms large flat terraces after annealing. The Au passivated surface shows a moiré pattern on the surface that is absent before annealing.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…Figure 1c,d shows representative STM topographic images of Co films on Au(111) surface before (1c) and after (1d) annealing. The morphology is similar to previous results [ 40,43 ] and shows that the Co film is dominated by random islands without thermal annealing but forms large flat terraces after annealing. The Au passivated surface shows a moiré pattern on the surface that is absent before annealing.…”
Section: Resultssupporting
confidence: 89%
“…The moiré structure is characteristic for the lattice misfit between Co and Au and has also been observed on thinner Co films on Au(111). [ 43,47,48 ] After annealing, the orientation of magnetization in the Co film was verified to be in‐plane by in situ magneto‐optical Kerr effect (MOKE) measurements, showing a low coercivity of ≈ 5 mT (see Figure , Supporting Information). After these processes, the [Fe II (Pyrz) 2 ] molecules were deposited onto the substrate held at room temperature from a Knudsen cell at 175°.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This represents a strain of between 10–15%, which may be observed in a pseudomorphic monolayer, but is vanishingly unlikely to persist in a film more than 7 ML thick. The same group has reported that the lattice parameter reverts to the Co bulk value at 7 ML, in a LEED study of the Co film without C 60 molecules present . 2.…”
Section: Resultsmentioning
confidence: 92%
“…The same group has reported that the lattice parameter reverts to the Co bulk value at 7 ML, in a LEED study of the Co film without C 60 molecules present. 33 2. In some cases, the domains coexist on the same layer.…”
Section: ■ Methodsmentioning
confidence: 99%